Re-visiting the six-item Stanford presenteeism scale (SPS-6) and its psychometric properties - Bezzina, Frank; Zielińska, Agnieszka; Cassar, Vincent (Frontiers in Psychology, 2023)
Presenteeism has often been considered as the correlate of absenteeism and associated to productivity loss. This study sought to re-examine the psychometric properties of the 6-item Stanford Presenteeism Scale (SPS-6), a popular measure which has been translated in a number of languages. The study adopted a cross-sectional design with 268 participants aged 18 - 65 working in a multinational IT company with headquarters based in Poland. The respondents participated willingly in an online questionnaire on a presenteeism health-related productivity measure (SPS-6), job resources (peer support), job demands (work-to-family conflict), engagement and burnout. Their responses were subjected to statistical analyses. Confirmatory Factor Analysis revealed that the SPS-6 is better represented by two singular and independent components, namely completing work and avoiding distractions, rather than an aggregated measure of health-related productivity. In fact, the aggregated measure had convergent and discriminant validity issues. We also assessed, via Structural Equation Modeling (SEM), the explanatory role of the SPS-6 within the wider well-being discourse by subjecting its’ factors as outcomes using the JD-R framework. Here, burnout was better at explaining its relationship to avoiding distractions and completing work compared to engagement, while avoiding distractions was more dominant than completing work in explaining indirect pathways. Given the convergent and discriminant validity of its two-dimensional measures, we argue that the SPS-6 is a better assessment of health-related productivity in the light of presenteeism when keeping both components separate rather than adding the scores from both dimensions to provide a global score as has been the practice so far. In addition, the SEM findings suggest that both SPS-6 components may require different theoretical explanations. This study supports a growing chorus of scholars who argue the need to look deeper into the presenteeism phenomenon, not least its measures.